Increased autism incidence: is there a single cause? - Crawford, Sarah (Journal of Child and Adolescent Behavior, 2016)
Keywords: dept.bio

Anti-inflammatory/antioxidant use in long-term maintenance cancer therapy: a new therapeutic approach to disease progression and recurrence. - Crawford, Sarah (Therapeutic advances in medical oncology, 2014)
The chronic, progressive clinical characteristics of many adult solid tumor malignancies suggest that a more effective therapeutic approach to cancer management may require long-term intervention using nontoxic systemic agents that block critical components of abnormal tumor physiology. Two highly promising systemic targets common to the development, progression and recurrence of many common cancers are dysregulated inflammatory and oxidation/reduction (redox) pathways. Compelling clinical data support the use of anti-inflammatory and antioxidant agents as a therapeutic modality for long-term use in patients diagnosed with several common cancers, including colon cancer and breast cancer. The therapeutic paradigm presented in this paper is the product of a synthesis of what is currently understood about the biological effects of inflammation and oxidative stress that contribute to tumorigenesis, disease progression and recurrence as well as results obtained from research on the use of prophylactics with anti-inflammatory or antioxidant properties in cancer prevention and treatment.
Keywords: anti-inflammatory agents; antiinflammatory agent; antioxidant; antioxidants; axitinib; bevacizumab; bosutinib; breast cancer; cabozantinib; cancer epidemiology; cancer growth; cancer recurrence; cancer therapy; cetuximab; chemoprophylaxis; chemotherapy; colon cancer; crizotinib; dasatinib; dept.bio; erlotinib; everolimus; gefitinib; human; imatinib; inflammation; ipilimumab; lapatinib; long term care; long-term maintenance cancer therapy; meta analysis (topic); nilotinib; nonhuman; oxidative stress; panitumumab; pazopanib; ponatinib; priority journal; randomized controlled trial (topic); reactive oxygen metabolite; regorafenib; review; ruxolitinib; sorafenib; sunitinib; systematic review (topic); temsirolimus; tofacitinib; trastuzumab; trastuzumab emtansine; unindexed drug; vandetanib; vemurafenib

The long journey of stem cell therapeutics. - Crawford, Sarah (Genome Medicine, 2012)
A report on the Euroepistem 2011 meeting 'Epigenomic Programming and Stem Cells for Drug Discovery', Paris, France, 21-22 November 2011.
Keywords: Article; dept.bio; embryonic stem cell; epigenetics; gene; gene silencing; human; induced pluripotent stem cell; nonhuman; priority journal; stem cell transplantation; transcription regulation

Is it time for a new paradigm for systemic cancer treatment? Lessons from a century of cancer chemotherapy. - Crawford, Sarah (Frontiers in pharmacology, 2013)
U.S. SEER (Surveillance Epidemiology and End Results) data for age-adjusted mortality rates for all cancers combined for all races show only a modest overall 13% decline over the past 35 years. Moreover, the greatest contributor to cancer mortality is treatment-resistant metastatic disease. The accepted therapeutic paradigm for the past half-century for the treatment of advanced cancers has involved the use of systemic chemotherapy drugs cytotoxic for cycling cells (both normal and malignant) during DNA synthesis and/or mitosis. The failure of this therapeutic modality to achieve high-level, consistent rates of disease-free survival for some of the most common cancers, including tumors of the lung, colon breast, brain, melanoma, and others is the focus of this paper. A retrospective assessment of critical milestones in cancer chemotherapy indicates that most successful therapeutic regimens use cytotoxic cell cycle inhibitors in combined, maximum tolerated, dose-dense acute treatment regimens originally developed to treat acute lymphoblastic leukemia and some lymphomas. Early clinical successes in this area led to their wholesale application to the treatment of solid tumor malignancies that, unfortunately, has not produced consistent, long-term high cure rates for many common cancers. Important differences in therapeutic sensitivity of leukemias/lymphomas versus solid tumors can be explained by key biological differences that define the treatment-resistant solid tumor phenotype. A review of these clinical outcome data in the context of recent developments in our understanding of drug resistance mechanisms characteristic of solid tumors suggests the need for a new paradigm for the treatment of chemotherapy-resistant cancers. In contrast to reductionist approaches, the systemic approach targets both microenvironmental and systemic factors that drive and sustain tumor progression. These systemic factors include dysregulated inflammatory and oxidation pathways shown to be directly implicated in the development and maintenance of the cancer phenotype. The paradigm stresses the importance of a combined preventive/therapeutic approach involving adjuvant chemotherapies that incorporate anti-inflammatory and anti-oxidant therapeutics.
Keywords: Adjuvant; Anti-inflammatory; Anti-oxidant; Chemotherapy; Drug resistance; Neoplasm; Tumor microenvironment; Vinca alkaloid; acute lymphoblastic leukemia; adjuvant therapy; advanced cancer; aminopterin; antibiotic agent; antineoplastic activity; antineoplastic agent; antioxidant; article; bladder cancer; bleomycin; brain cancer; breast cancer; cancer cell; cancer chemotherapy; cancer growth; cancer mortality; cancer recurrence; cancer regression; cancer resistance; cancer survival; carboplatin; carmustine; chemosensitivity; childhood leukemia; chlorambucil; chlormethine; choriocarcinoma; cisplatin; colon cancer; cyclophosphamide; dept.bio; disease activity; disease free survival; doxorubicin; drug intermittent therapy; drug megadose; drug tolerability; drug treatment failure; elastin; etoposide; fludarabine; fluorouracil; gemcitabine; head and neck cancer; human; hydroxyurea; infection; inflammation; leukemia; lung cancer; lymphoma; malignant neoplastic disease; maximum tolerated dose; melanoma; mercaptopurine; metastasis; methotrexate; mitoxantrone; multiple cycle treatment; multiple myeloma; nonhodgkin lymphoma; nonhuman; ovary cancer; ovary carcinoma; paclitaxel; pancreas cancer; phenotype; platinum complex; prednisone; procarbazine; solid tumor; systemic therapy; testis cancer; topotecan; tumor microenvironment; unindexed drug; vinblastine; vinblastine sulfate; vincristine

Virus/host multicellular adaptation: a model of the evolutionary basis for multicellularity and the origins of cancer - Crawford, Sarah (SSRN Electronic Journal, 2026)
Keywords: Cancer cell; Cell; Cell fate determination; Cellular differentiation; Immune system; Intracellular; Morphogenesis; Multicellular organism; Receptor; dept.bio

Autism risk: What do vaccines have to do with - Crawford, Sarah Adelaide (Academic Journal of Pediatrics & Neonatology, 2017)
Keywords: dept.bio; ⚠️ Invalid DOI

A “chaotic” approach to the treatment of advanced cancer - Crawford, Sarah Adelaide (Journal of Traditional Medicine & Clinical Naturopathy, 2017)
Keywords: dept.bio

Autism vs vaccines: The power of observation - Crawford, Sarah Adelaide (Journal of Autism and Epilepsy, 2018)
Keywords: dept.bio; peer-reviewed; ⛔ No DOI found

Autism vs vaccines: The case reopened - Crawford, Sarah Adelaide (Journal of Autism and Epilepsy, 2018)
Keywords: dept.bio; peer-reviewed; ⛔ No DOI found

The gene book: Explorations in the code of life - Crawford, Sarah Adelaide (Cognella Academic Publishing, 2018)
The Gene Book: Explorations in the Code of Life is designed to introduce undergraduate college students to foundational concepts in genetics. The text provides in-depth coverage of the essential principles of genetics, from Mendel to molecular gene therapy, and reads like a story, guiding readers through each of these areas in an interesting, engaging, and enlightening way.  Milestone scientific discoveries introduce conceptual topics in each of the 10 chapters. The significance of each genetics paradigm is reinforced by the meaningful research context in which it is placed, whether the focus is single gene inheritance of disorders such as PKU and cystic fibrosis, or more complex genetic phenomena. Chromosomes, cell division, and cytogenetic disorders, including Down Syndrome and leukemia, are presented in a riveting historical context. In addition, the principles of molecular genetics are a major focus of this book. Students learn about the double helix, DNA replication, gene expression, mutation, natural selection, genomics, and the tools of molecular DNA analysis.  Approachable and effective, The Gene Book is a highly readable comprehensive text on genetics principles designed to highlight essential concepts that make up their very core. The text is well suited to undergraduate genetics courses and can also be used as a primer for more advanced undergraduate and graduate courses in medial or molecular genetics.Sarah Adelaide Crawford is professor of genetics at Southern Connecticut State University. Dr. Crawford received a Ph.D. from Columbia University College of Physicians and Surgeons, an M.S. degree in biochemistry from Princeton University, and a B.S. degree from Marymount Manhattan College. She is director of the Cancer Biology Research Laboratory and the recently opened the Autism Research Laboratory at the Southern Connecticut State University.
Keywords: dept.bio

Is it time to begin prenatal/neonatal screening for autism risk? - Crawford, Sarah Adelaide (Global Journal of Pediatrics & Neonatal Care, 2019)
Keywords: dept.bio; peer-reviewed

Formulations comprising extracts from primitive plant species (mosses, ferns and lichens) to treat and prevent cancers - Crawford, Sarah; Boisvert, Erin (2007)
Keywords: dept.bio; ⛔ No DOI found

Identification of novel cell components designated “tissue organizing structures”* with potential applications in cancer prevention/therapeutics, tissue bioengineering, and gene therapy - Crawford, Sarah; Herbert, Tasino; Potter, Herbert (Cancer Epidemiology and Prevention Biomarkers, 2007)
Keywords: dept.bio; ⛔ No DOI found

Tissue organizing structure and therapeutic methods - Crawford, Sarah; Potter, Herbert; Herbert, Tasino (2008)
Keywords: dept.bio; ⛔ No DOI found

Abstract A57: Lipid extract from the ostrich fern Matteucia struthiopteris displays potent anti-cancer effects in microtumors from human malignant cell lines via disruption of actin cytoskeleton - Crawford, Sarah; Penarreta, Rafaella; Diamond, Deanna (Cancer Prevention Research, 2008)
Keywords: dept.bio

Estrogen dependent growth inhibitory effects of tamoxifen but not genistein in solid tumors derived from estrogen receptor positive (ER+) primary breast carcinoma MCF7: single agent and novel combined treatment approaches. - Nobert, Gayle S; Kraak, Martha M; Crawford, Sarah (Bulletin du cancer, 2006)
While many studies have documented tamoxifen's benefits as an adjuvant therapy in the treatment and prevention of recurrent breast cancer in estrogen receptor positive (ER+) breast carcinoma, this beneficial effect may decrease with long-term tamoxifen use. This experimental study was designed to compare the cytotoxic responses of ER+ primary breast cancer solid tumors derived from the MCF7 cell line to experimental therapeutics, including genistein, tamoxifen, all-trans retinoic acid (ATRA) and parthenolide in the presence and absence of exogenous beta-estradiol. The results of this study suggest that the growth inhibitory effects of tamoxifen, were dependent on beta-estradiol levels. In contrast, the cytotoxic effects of the isoflavone soy derivative, genistein, were observed to be independent of exogenous estrogen. Moreover, combined therapy using tamoxifen and genistein produced enhanced cytotoxic effects also independent of beta-estradiol levels. Additional studies involving the use of the novel agents all trans retinoic acid (ATRA) and parthenolide produced notable tumor responses and combined effects that were also estrogen-independent. Overall, these preclinical research findings suggest possible clinical applications suggesting that genistein might be a useful clinical adjuvant, particularly in post-menopausal women in whom breast cancer occurs more frequently. Moreover, this research suggests that combined treatment approaches involving the use of tamoxifen in conjunction with agents that inhibit NFkappaB pathway signaling, such as parthenolide and genistein, warrant further study.
Keywords: *Antineoplastic Combined Chemotherapy Protocols/tu [Therapeutic Use]; *Breast Neoplasms/dt [Drug Therapy]; *Genistein/tu [Therapeutic Use]; *Neoplasms, Hormone-Dependent/dt [Drug Therapy]; *Tamoxifen/tu [Therapeutic Use]; Anticarcinogenic Agents; Anticarcinogenic Agents/tu [Therapeutic Use]; Antineoplastic Agents, Hormonal; Antineoplastic Agents, Hormonal/tu [Therapeutic Use]; Antineoplastic Combined Chemotherapy Protocols; Breast Neoplasms; Breast Neoplasms/ch [Chemistry]; Cell Line, Tumor; Dose-Response Relationship, Drug; Drug Resistance, Neoplasm; Drug Resistance, Neoplasm/de [Drug Effects]; Estradiol; Estradiol/pd [Pharmacology]; Female; Genistein; Humans; Neoplasms, Hormone-Dependent; Neoplasms, Hormone-Dependent/ch [Chemistry]; Receptors, Estrogen; Sesquiterpenes; Sesquiterpenes/tu [Therapeutic Use]; Spheroids, Cellular; Spheroids, Cellular/de [Drug Effects]; Tamoxifen; Tretinoin; Tretinoin/tu [Therapeutic Use]; antineoplastic agent; antineoplastic hormone agonists and antagonists; article; breast tumor; chemistry; dept.bio; dose response; drug effect; drug resistance; estradiol; estrogen receptor; female; genistein; human; multicellular spheroid; neoplasm; parthenolide; retinoic acid; sesquiterpene; tamoxifen; tumor cell line; ⛔ No DOI found

Effect of increased extracellular Ca++ on microvesicle production and tumor spheroid formation - Crawford, Sarah; Diamond, Deanna; Brustolon, Laura; Penarreta, Rafaela (Cancer microenvironment : official journal of the International Cancer Microenvironment Society, 2011)
Research on the composition of the tumor micro-environment has demonstrated that membrane delimited microvesicles are shed from many types of malignant tumors, in the peripheral blood of cancer patients as well as in culture media of tumor cells propagated in vitro (Ginestra et al. Anticancer Res 18:3433-3437, 1998). Their documented effects involve the activation of signal transduction pathways by cellular cross-talk that are associated with epigenetic mechanisms that may be important in tumor progression, metastasis, and the activation of angiogenesis (Distler et al. Arthritis Rheum 52:3337-3348, 2005). Live cell imaging microscopic studies conducted in our laboratory of the formation of solid tumor spheroids in vitro show that the shedding of microvesicular structures from tumor cells occurs during this process. The observed properties of the tumor microvesicles suggest a role in solid tumor formation and intercellular communication. The tumor associated microvesicles were shown to be non-apoptotic based on the absence of fluorescent nuclear staining by acridine orange/ethidium bromide staining. Increased concentration of extracellular Ca(++) [5-20 mM] resulted in an increase in the production of tumor-derived microvesicles and also to result in the formation of tumor spheroids whose size was considerably smaller than controls. Increased extracellular [Ca(++)] was also observed to induce the rapid dissociation of solid tumor spheroids to smaller cell aggregates in the absence of significant apoptosis.
Keywords: Extracellular Ca++; Live cell imaging; Multicellular tumor spheroid; Tumor associated microvesicle; acridine orange; angiogenesis; apoptosis; article; breast carcinoma; calcium ion; cancer cell culture; cell aggregation; cell nucleus; concentration (parameters); controlled study; cytochemistry; dept.bio; epigenetics; ethidium bromide; extracellular calcium; glioblastoma; human; human cell; in vitro study; membrane vesicle; metastasis potential; microscopy; molecular interaction; osteosarcoma; priority journal; signal transduction; tumor growth; tumor microenvironment; tumor spheroid; tumor vascularization

Abstract 776: Anticancer properties of phytochemical extracts from native New England species of ferns in breast cancers of diverse genetic backgrounds - Crawford, Sarah; Diamond, Deanna; Penarreta, Rafaela; Brustolon, Laura; Wang, Hua; Hanks, Judith Garrison; Barbieri, Zachary (Cancer Research, 2010)
Keywords: dept.bio

Cancer prevention and therapy through the modulation of the tumor microenvironment. - Casey, Stephanie C; Amedei, Amedeo; Aquilano, Katia; Azmi, Asfar S; Benencia, Fabian; Bhakta, Dipita; Bilsland, Alan E; Boosani, Chandra S; Chen, Sophie; Ciriolo, Maria Rosa; Crawford, Sarah; Fujii, Hiromasa; et al. (Seminars in Cancer Biology, 2015)
Cancer arises in the context of an in vivo tumor microenvironment. This microenvironment is both a cause and consequence of tumorigenesis. Tumor and host cells co-evolve dynamically through indirect and direct cellular interactions, eliciting multiscale effects on many biological programs, including cellular proliferation, growth, and metabolism, as well as angiogenesis and hypoxia and innate and adaptive immunity. Here we highlight specific biological processes that could be exploited as targets for the prevention and therapy of cancer. Specifically, we describe how inhibition of targets such as cholesterol synthesis and metabolites, reactive oxygen species and hypoxia, macrophage activation and conversion, indoleamine 2,3-dioxygenase regulation of dendritic cells, vascular endothelial growth factor regulation of angiogenesis, fibrosis inhibition, endoglin, and Janus kinase signaling emerge as examples of important potential nexuses in the regulation of tumorigenesis and the tumor microenvironment that can be targeted. We have also identified therapeutic agents as approaches, in particular natural products such as berberine, resveratrol, onionin A, epigallocatechin gallate, genistein, curcumin, naringenin, desoxyrhapontigenin, piperine, and zerumbone, that may warrant further investigation to target the tumor microenvironment for the treatment and/or prevention of cancer. Copyright © 2015 Elsevier Ltd. All rights reserved.
Keywords: *Carcinogenesis/de [Drug Effects]; *Neoplasms/dt [Drug Therapy]; *Neovascularization, Pathologic/dt [Drug Therapy]; *Tumor Microenvironment/ge [Genetics]; 5 chloro n2 [1 (5 fluoro 2 pyrimidinyl)ethyl] n4 (5 methyl 1h pyrazol 3 yl) 2,4 pyrimidinediamine; Antineoplastic Agents; Antineoplastic Agents/tu [Therapeutic Use]; Cancer biology; Cancer prevention; Cancer therapy; Carcinogenesis; Carcinogenesis/ge [Genetics]; Cell Proliferation; Cell Proliferation/de [Drug Effects]; Humans; Janus kinase; Molecular Targeted Therapy; Neoplasms; Neoplasms/ge [Genetics]; Neoplasms/pc [Prevention & Control]; Neovascularization, Pathologic; Neovascularization, Pathologic/ge [Genetics]; Neovascularization, Pathologic/pc [Prevention & Control]; Review; Signal Transduction; Tumor Microenvironment; Tumor Microenvironment/de [Drug Effects]; Tumor microenvironment; antiinflammatory activity; antineoplastic agent; antioxidant activity; antiproliferative activity; apoptosis; bacterial infection; berberine; bevacizumab; cancer prevention; cancer therapy; candidiasis; carcinogenesis; cell proliferation; cholesterol synthesis; cisplatin; colorectal cancer; curcumin; cytokine production; dendritic cell; dept.bio; desoxyrhapontigenin; drug cytotoxicity; drug effects; drug potentiation; drug structure; drug targeting; endoglin; epigallocatechin gallate; fatty liver; fibrosis; genetics; genistein; genomic instability; glioblastoma; human; hydroxymethylglutaryl coenzyme A reductase inhibitor; hypercholesterolemia; hyperlipidemia; hypoxia; indoleamine 2,3 dioxygenase; interleukin 6; kidney cancer; liver cancer; liver cell carcinoma; lung cancer; lung metastasis; macrophage activation; metastasis inhibition; molecularly targeted therapy; mycosis; naringenin; natural product; non insulin dependent diabetes mellitus; nonhuman; obesity; oncogene; onionin A; paclitaxel; pancreas tumor; parasitosis; piperine; reactive oxygen metabolite; resveratrol; signal transduction; sorafenib; stomach cancer; sunitinib; tamoxifen; tumor associated leukocyte; tumor escape; tumor invasion; tumor microenvironment

Designing a broad-spectrum integrative approach for cancer prevention and treatment. - Block, Keith I; Gyllenhaal, Charlotte; Lowe, Leroy; Amedei, Amedeo; Amin, A R M Ruhul; Amin, Amr; Aquilano, Katia; Arbiser, Jack; Arreola, Alexandra; Arzumanyan, Alla; Ashraf, S Salman; Azmi, Asfar S; et al. (Seminars in Cancer Biology, 2015)
Targeted therapies and the consequent adoption of "personalized" oncology have achieved notable successes in some cancers; however, significant problems remain with this approach. Many targeted therapies are highly toxic, costs are extremely high, and most patients experience relapse after a few disease-free months. Relapses arise from genetic heterogeneity in tumors, which harbor therapy-resistant immortalized cells that have adopted alternate and compensatory pathways (i.e., pathways that are not reliant upon the same mechanisms as those which have been targeted). To address these limitations, an international task force of 180 scientists was assembled to explore the concept of a low-toxicity "broad-spectrum" therapeutic approach that could simultaneously target many key pathways and mechanisms. Using cancer hallmark phenotypes and the tumor microenvironment to account for the various aspects of relevant cancer biology, interdisciplinary teams reviewed each hallmark area and nominated a wide range of high-priority targets (74 in total) that could be modified to improve patient outcomes. For these targets, corresponding low-toxicity therapeutic approaches were then suggested, many of which were phytochemicals. Proposed actions on each target and all of the approaches were further reviewed for known effects on other hallmark areas and the tumor microenvironment. Potential contrary or procarcinogenic effects were found for 3.9% of the relationships between targets and hallmarks, and mixed evidence of complementary and contrary relationships was found for 7.1%. Approximately 67% of the relationships revealed potentially complementary effects, and the remainder had no known relationship. Among the approaches, 1.1% had contrary, 2.8% had mixed and 62.1% had complementary relationships. These results suggest that a broad-spectrum approach should be feasible from a safety standpoint. This novel approach has potential to be relatively inexpensive, it should help us address stages and types of cancer that lack conventional treatment, and it may reduce relapse risks. A proposed agenda for future research is offered. Copyright © 2015 The Authors. Published by Elsevier Ltd.. All rights reserved.
Keywords: *Genetic Heterogeneity; *Molecular Targeted Therapy; *Neoplasms/th [Therapy]; *Precision Medicine; Antineoplastic Agents, Phytogenic; Antineoplastic Agents, Phytogenic/tu [Therapeutic Use]; Cancer hallmarks; Drug Resistance, Neoplasm; Drug Resistance, Neoplasm/ge [Genetics]; Genetic Heterogeneity; Humans; Integrative medicine; Molecular Targeted Therapy; Multi-targeted; Neoplasms; Neoplasms/ge [Genetics]; Neoplasms/pa [Pathology]; Neoplasms/pc [Prevention & Control]; Phytochemicals; Precision Medicine; Review; Signal Transduction; Targeted therapy; Tumor Microenvironment; Tumor Microenvironment/ge [Genetics]; anthocyanin; antineoplastic activity; antineoplastic agent; apoptosis; belinostat; berberine; breast cancer; cancer prevention; cancer therapy; cell immortalization; colorectal cancer; curcumin; deguelin; dept.bio; dietary intake; dinaciclib; drug cost; drug efficacy; drug resistance; drug safety; drug targeting; enterolactone; epigallocatechin gallate; gamma linolenic acid; genetic heterogeneity; genetics; genistein; genomic instability; gossypol; human; icosapentaenoic acid; imetelstat; inflammation; integrative medicine; interdisciplinary communication; kaempferol; luteolin; lycopene; melatonin; metastasis; metastasis inhibition; molecularly targeted therapy; naringenin; natural product; nonhuman; palbociclib; patent; pathology; perillyl alcohol; personalized medicine; phenotype; phytochemistry; recurrence risk; resveratrol; risk reduction; romidepsin; selinexor; signal transduction; silibinin; soybean; triptolide; tumor escape; tumor invasion; tumor microenvironment; tumor vascularization; unindexed drug; vorinostat; withaferin A; zerumbone